Employee Performance from a Behavioral Accounting Perspective - Ni Putu Candra Ulan Sari; Rahayu Indriasari; Nina Yusnita Yamin; Latifah Sukmawati Yuniar (Sean Institute, 2025)
This study aims to examine in deepth the application of behavioral accounting performance performance measurement in Talise Valangguni Village. This research can provide information on how good performance in an organization within the scope of behavioral accounting. The research method used is a qualitative research method with a descriptive approach. Data collection using the interview method. The results showed that the application of behavioral accounting was not fully good. Performance measurement uses indicators of work quality; work quantity; timeliness; effectiveness and independence.